Resource Monitoring Model in Cloud Computing Based on Dynamic Period and Event-Driven - Ping Guo; Tingying Feng (Dianxin kexue)
Resource monitoring in cloud computing environment is a significant part of cloud computing platform for resource management, which provides a basis for resource allocation, task scheduling and load balancing, etc. According to the characteristics of cloud computing resources, this paper put forward a monitoring model based on dynamic period and event-driven, and it has excellent timeliness, robustness, loose coupling and scalable by combining dynamic period and event-driven monitoring. The model can collect real-time resource monitoring information, and discover the faults of cloud computing environment timely and meet the need of cloud computing platform.